Caulonia tra Crotone e Locri Atti del Convegno Internazionale, Firenze 30 maggio-1 giugno 2007 - Lepore, Lucia; Turi, Paola (Atti, 2010)
The work comprises over 30 original contributions and is completed by numerous illustrations, drawings and plans. The topics addressed include historic sources, topography, architecture, town planning, religion, funereal ideology, musical culture, epigraphy, coinage, craftsmanship and metallurgy as well as applied sciences and technologies. The articles are remarkable in terms of a new approach to the reading of the historic events and archaeological problems of the Achaean colony of Caulonia within a broader territorial dimension that also takes in Crotone and Locri.